Water absorptive dressing composite material
The dressing composite material with a coating film, adhesive layer, and water-absorbent pad addresses exudate absorption issues, maintaining adhesion and preventing peeling, thus enhancing wound care efficacy and reducing costs.
Patent Information
- Application Number
- JP2024122895
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-28
- Filing Date
- 2024-07-29
- Publication Date
- 2025-02-07
AI Technical Summary
Existing wound dressing materials fail to effectively absorb exudate, leading to peeling, dirt, and infection risks, with complex specifications and high costs.
A dressing composite material comprising a coating film, an adhesive layer with hydrophilic adhesives and water-absorbing components, and a water-absorbent pad, designed for excellent moisture permeability and adhesion, preventing exudate leakage.
The composite material effectively absorbs exudate, maintains adhesion, and prevents peeling, ensuring easy use and lower manufacturing costs while reducing infection risks.
Smart Images

Figure 2025020052000009 
Figure 2025020052000010 
Figure 2025020052000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a water-absorbent dressing composite material used for protecting a wound or fixing a catheter, etc. [Background technology]
[0002] Dressing materials that are applied to the skin are widely used for the purpose of protecting wounds and fixing catheters used for infusions. Dressing materials generally consist of a base material, an adhesive layer applied to one side of the base material, and a release sheet that covers the adhesive layer. The base material of such dressing materials is made of polyurethane film, which is flexible and adapts well to the skin after application, so that it does not cause any discomfort.
[0003] For example, Patent Document 1 states that the moisture permeability is 2,000 g / m 2 - Support for 24 hours or more and moisture permeability of 2,500g / m 2 - Patches with an adhesive layer lasting 24 hours or more are listed. However, although the above patches are moisture permeable, they have a water-absorbent base material and a non-absorbent adhesive layer, so if exudate or the like comes out of the wound, it will not be absorbed by the dressing material and will leak out, causing peeling, staining, and infection.
[0004] Patent Document 2 describes a dressing material that is made of a transparent or semi-transparent covering film made of polyurethane or polyethylene, a water-absorbent padding material, and an adhesive layer laminated to the covering film. However, the water-absorbent padding material has a through-hole that allows easy observation of the catheter insertion site, and the adhesive layer in the area that comes into contact with the skin is not water-absorbent, so that if exudate leaks out, the dressing material may come off.
[0005] Patent document 3 describes a dressing material that is composed of a base having an opening for passing a catheter from the catheter site, a portion that is folded over and fixed to the base to surround the catheter, and a cover portion that can be peeled off from the base. However, the specifications are complicated and difficult to use, and production is too costly, making it unusable in actual situations.
[0006] Patent Document 4 describes a dressing material in which the adhesive layer is doubled, the first adhesive layer is applied to the skin, the release paper is peeled off, and a catheter is applied to the other side. Finally, a second adhesive is applied over the catheter to fix it in place. This dressing material has a simple structure and can be used on wounds, making it easy to use. However, since it is not layered with an absorbent pad material, if exudate leaks from the catheter site, the dressing material may peel off, become dirty, or become infected. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2021-183051 A [Patent Document 2] Japanese Patent Application Publication No. 5-285224 [Patent Document 3] JP 2018-956 A [Patent Document 4] JP 2014-104055 A Summary of the Invention [Problem to be solved by the invention]
[0008] Usually, dressings applied to wound sites are semi-transparent or transparent films that allow the catheter insertion site to be visualized, but many of them have weak adhesive properties and are prone to floating or peeling off due to exudate from the affected area. If the dressing floats, the surrounding area can easily become dirty and become a cause of infection. In addition, in order to adequately fix the catheter, the specifications of the dressing material become complicated, which makes the method of use complicated and increases the manufacturing costs. An object of the present invention is to provide a composite dressing material having excellent moisture permeability and water resistance, which can be applied to a wound for the purpose of protecting the wound and can also be used to fix a catheter. [Means for solving the problem]
[0009] The present inventors have found that the initial object can be achieved by using materials and components in a dressing that have excellent absorbency for moisture that exudes from the skin while the dressing is being applied, and have thus completed the present invention. The present invention is as follows. [1] A composite dressing material having a covering film having a moisture permeability of 1,200 g / m2·24 h or more, an adhesive layer laminated on the entire surface of the covering film, and a water-absorbent pad material adhered to the adhesive layer, the adhesive layer comprises a hydrophilic acrylic adhesive or a urethane adhesive, or a mixture of these adhesives, and the adhesive layer further comprises one or more water-absorbing components selected from the group consisting of polyvinyl alcohol, polyvinylpyrrolidone, polyacrylamide, polyacrylic acid, sodium polyacrylate, methylcellulose, ethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, carboxymethylcellulose, alginic acid, propylene glycol alginate, agarose, chitosan, hyaluronic acid and hyaluronic acid derivatives, chondroitin sulfate, starch, pectin, tragacanth gum, xanthan gum, guar gum, and carrageenan; The absorbent pad material is a water-absorbent soft urethane foam or a pad having a basis weight of 100 g / m 2A water-absorbent composite dressing material comprising the above nonwoven fabric. [2] The absorbent dressing composite material described in [1], in which a release sheet is attached to the surface of the adhesive layer opposite to the surface that contacts the cover film, and the absorbent pad material is enclosed between the cover film and the release sheet. [3] The water-absorbent dressing composite material according to [1], wherein the adhesive strength of the adhesive layer is 0.4 N / 20 mm or more in the presence of moisture. [4] The water-absorbent dressing composite material according to [1], wherein the covering film is a polyurethane resin having a thickness of 5 to 30 μm, the adhesive layer is a composition containing an acrylic polymer having a thickness of 10 to 80 μm, and the water-absorbent component is contained in the adhesive layer at 0.1 to 30% by mass. [5] The water absorption capacity of the water-absorbing pad material is 0.01 g / cm 2 The absorbent dressing composite material described in [1] above. [6] The absorbent dressing composite material according to any one of [1] to [5], wherein the absorbent pad material has a rectangular or square shape with each side measuring 30 mm to 50 mm, or a circular or elliptical shape with a diameter of 30 mm to 50 mm, and the peripheral portion is hollowed out to a size of approximately 10 mm, so that exudate leaking from the catheter does not leak out. [7] The absorbent dressing composite material according to [1], wherein the adhesive layer contains a tackifier. Effect of the Invention
[0010] The composite dressing of the present invention is composed of a covering film, an adhesive layer containing a water-absorbing component laminated thereon, an absorbent pad attached to the adhesive layer, and a release sheet. Because the covering film and the adhesive layer containing a water-absorbing component are laminated together, the adhesive layer and the absorbent pad can absorb water even if the adhesive surface of the skin is wet with exudate, so that the dressing material can be prevented from floating or peeling off. The product of the present invention is applied by peeling off the release sheet when in use, and has a simple structure, excellent usability, and can be produced at low cost. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a plan view of an example of a dressing composite of the present invention. [Diagram 2] 2 is a cross-sectional view taken along line AA' in FIG. [Diagram 3] FIG. 2 is a plan view showing another example of a dressing composite of the present invention. [Figure 4] FIG. 2 is a plan view showing yet another example of a dressing composite of the present invention. [Diagram 5] FIG. 2 is a plan view showing yet another example of a dressing composite of the present invention. [Figure 6] FIG. 2 is a plan view showing yet another example of a dressing composite of the present invention. [Figure 7] FIG. 2 is a plan view showing yet another example of a dressing composite of the present invention. [Figure 8] FIG. 2 is a plan view showing yet another example of a dressing composite of the present invention. [Figure 9] FIG. 8 is a plan view showing an example of a catheter attached to the composite dressing of FIG. 7. [Figure 10] FIG. 9 is a plan view showing an example of a catheter attached to the composite dressing of FIG. 8. [Figure 11] 10 is a cross-sectional view taken along line BB' in FIG. [Figure 12] 1 is a cross-sectional view of yet another example of a dressing composite of the present invention, in which a tag is attached to the covering film. [Figure 13] FIG. 2 is a plan view showing an example of a dressing composite of the present invention with a tag. [Figure 14] FIG. 13 is a plan view showing another example of a dressing composite of the present invention with a tag. [Figure 15] FIG. 13 is a plan view showing another example of a dressing composite of the present invention with a tag. [Figure 16] FIG. 13 is a plan view showing another example of a dressing composite of the present invention with a tag. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The composite dressing of the present invention is composed of a cover film, an adhesive layer, and an absorbent pad, with a release sheet attached to protect the surfaces of the adhesive layer and the absorbent pad.
[0013] The covering film used in the present invention is required to be transparent, moisture permeable, and flexible. Polyurethane is a suitable material, but the moisture permeability and flexibility of polyurethane vary greatly depending on the thickness of the film. The thickness of this covering film is preferably 3 to 40 μm, and more preferably 5 to 30 μm. The moisture permeability is 1,200 g / m 2 -24 hours or more is desirable. If it is thinner than 3μm, the strength of the film is low and it is easy to tear when applied. Also, if it is thicker than 40μm, the moisture permeability is low and the skin is easily steamed, so there is a high risk of skin irritation when applied for a long time.
[0014] The size of the covering film is not particularly limited, but when the wound site is small, it is a rectangle or square of 10-20 mm x 50-70 mm, with one side being an adhesive layer, and a water-absorbent pad smaller than the covering film (for example, 5-15 mm x 20-30 mm) is attached to it. When the wound site is large or when a catheter is to be fixed, the size of the covering film is usually a rectangle or square of 40-80 mm x 60-120 mm, preferably a rectangle or square of 60-80 mm x 80-100 mm, and can be appropriately selected depending on the type of catheter to be fixed (see Figures 9 and 10).
[0015] The adhesive constituting the adhesive layer may be HIPAS-10 (Cosmedy Pharmaceutical Co., Ltd.), a hydrophilic acrylic adhesive, or HIPAS-PU (Cosmedy Pharmaceutical Co., Ltd.), a urethane adhesive, which may be adjusted to an appropriate adhesive strength by adding a plasticizer as necessary. The adhesive may be applied to the covering film by a conventional method. The thickness of this adhesive layer is 10 to 80 μm, preferably 20 to 50 μm. This adhesive layer functions to fix the dressing composite to the patient's skin in areas other than the area in contact with the pad, so it is preferable for the adhesive layer to cover the entire surface or most of the surface of the covering film.
[0016] Examples of the water-absorbing component that is blended into the adhesive layer to increase the hydrophilicity of the adhesive layer include synthetic polymers such as polyvinyl alcohol, polyvinylpyrrolidone, polyacrylamide, polyacrylic acid, sodium polyacrylate, methylcellulose, ethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, and carboxymethylcellulose, as well as polysaccharides and derivatives thereof such as alginic acid, propylene glycol alginate, agarose, chitosan, hyaluronic acid and hyaluronic acid derivatives, chondroitin sulfate, starch, pectin, tragacanth gum, xanthan gum, guar gum, and carrageenan. The blending amount of the water-absorbing component is preferably 0.1 to 30% by mass relative to the adhesive mass. If it is 30% by mass or more, it is difficult to uniformly disperse and dissolve the water-absorbing component in the adhesive layer, and the transparency is reduced, impairing the visibility of the dressing sheet. More preferably, it is 0.5 to 20% by mass, and optimally, it is 1 to 15% by mass. If it is 0.1% by mass or less, it is not desirable because sufficient water absorption cannot be obtained.
[0017] The water-absorbing component to be blended in the adhesive layer is preferably dissolved in ethanol or water, but it may also be dispersed in powder form without dissolving it. By dissolving and dispersing it, the transparency of the adhesive layer can be maintained and it can be blended uniformly.
[0018] In addition, a tackifier can be added to the adhesive layer as necessary to increase the adhesion between the skin and the covering film. When a water-absorbing component is added to the adhesive layer, the tack with the skin may be weakened, so adding a rosin-based component to the adhesive can prevent this problem. As the tackifier, polymerized rosin ester (Pencel: Arakawa Chemical Industries Co., Ltd.), rosin derivative (Pine Crystal: Arakawa Chemical Industries Co., Ltd.), and hydrogenated rosin ester (Ester Gum: Arakawa Chemical Industries Co., Ltd.) can be blended. The blending amount of the tackifier is preferably 1 to 30% by mass relative to the adhesive mass. If it exceeds 30% by mass or more, the adhesive layer becomes sticky, the adhesive remains on the skin, and the feel becomes poor. More preferably, it is 1 to 20% by mass, and optimally, it is 3 to 10% by mass. If it is less than 1% by mass, the improvement in adhesion is not sufficiently obtained, which is not preferable.
[0019] The peel strength from the skin of the adhesive layer according to the present invention is preferably 0.4 N / 20 mm or more, more preferably 0.5 to 1.5 N / 20 mm, and even more preferably 0.6 to 1.0 N / 20 mm. If the skin adhesive strength is too low, there is a risk of peeling during application, and if the skin adhesive strength is too high, there is a risk of pain occurring when peeling.
[0020] The water-absorbent pad material used in the present invention may be a foamed hydrophilic plastic such as soft urethane foam or a nonwoven fabric having high water absorbency. The highly absorbent nonwoven fabric has a basis weight of 100g / m 2 The above is preferable. Materials that can be used for the nonwoven fabric include highly absorbent cotton, pulp, rayon, polyester, and polyethylene. It is also possible to mix water-soluble polymers such as sodium polyacrylate, polyvinylpyrrolidone, and hyaluronic acid between the nonwoven fabric to produce and use a nonwoven fabric material with enhanced absorbency. The absorbent pad has a water absorption capacity of 0.01g / cm 2It is desirable that this be the case. Compared to nonwoven fabric, urethane foam absorbs more water, but the absorption speed is slower. In either case, it is ideal if the material starts absorbing water within one minute of application. On the other hand, nonwoven fabric can absorb water instantly, so the type of absorbent pad material to use can be selected depending on the application.
[0021] The shape of the absorbent pad material is not particularly limited, but it is preferable that the pad material be rectangular or square with sides of 30 to 50 mm, or circular, semicircular, or elliptical with a diameter of 30 to 50 mm, with the periphery cut out to about 10 mm, to prevent exudate leaking from the catheter. A rectangular or square absorbent pad material may be combined with a circular, semicircular, or elliptical absorbent pad material. For production efficiency, a pad material with a discontinuous periphery may be selected, as shown in Figure 1.
[0022] When fixing a catheter with a dressing, most conventional dressings are designed to come into direct contact with the catheter and the skin, which can cause the catheter to rub against the skin and cause skin damage or inflammation. To solve this problem, we provide a composite absorbent dressing (see Figures 7 and 8) that prevents the catheter from coming into direct contact with the skin by placing an absorbent pad material under the catheter, and then fixes it with a covering film with an adhesive layer attached from above. Finally, to protect the adhesive layer, it is covered with a release sheet; PET (polyethylene terephthalate), PE (polyethylene), PVC (polyvinyl chloride), or coated paper that has been treated with a release agent such as silicone can be used.
[0023] Next, the composite dressing of the present invention will be described in detail. Fig. 1 is a plan view of one embodiment of the composite dressing of the present invention, and Fig. 2 is a cross-sectional view taken along the line AA' in Fig. 1. An adhesive layer 2 is laminated on one side of a transparent or semi-transparent covering film 1, and a water-absorbent pad material 3 is adhered to the covering film 1 via this adhesive layer 2. After peeling off the release sheet 4, the dressing is applied to the skin.
[0024] The moisture permeability test of the coating film is carried out according to JIS L1099 A-1 method (calcium chloride method). Calcium chloride is placed in a specified cup and sealed with the prepared urethane film. It is left for 4 hours in an environment of 40°C and 90% humidity, and the amount of water vapor absorbed by the calcium chloride through the urethane film is measured.
[0025] The peel strength of the adhesive layer from the skin when applied to the skin is measured and evaluated by the following measurement method. The adhesive layer used in the present invention is cut into a test piece of 20 mm width x 150 mm length. The test piece is attached to a SUS304 mirror-finished plate in an atmosphere of 24°C temperature and 65% relative humidity, and pressed with a roller. After 30 minutes, the test piece is peeled off in the 90° direction at a peel speed of 300 mm / min, and the peel strength is measured.
[0026] The adhesive strength of the adhesive layer is measured according to the probe tack test method of the 17th revision of the Japanese Pharmacopoeia. The material of the adhesive strength test probe is SUS304, the surface roughness is root mean square roughness (Rq) of 250-500 nm, and the diameter is 5 mm. The urethane film with the adhesive layer adhered to it is attached to the weight ring without slack. Next, the probe is brought into contact with the adhesive surface of the urethane film at a speed of 10±0.01 mm per second, and a tack of 0.98±0.01 N / cm is measured. 2 The contact load is maintained for 1.0±0.1 seconds. Immediately after that, the probe is peeled off from the adhesive surface in a direction perpendicular to the adhesive surface at a speed of 10±0.01 mm per second, and the maximum load required to peel off the probe is the value of the probe tack test. The unit is N / cm 2 It is.
[0027] Furthermore, assuming that the patch will be applied to skin with leaked exudate, the adhesive layer is coated with water to confirm whether its adhesive strength decreases or not, using the following test method. To measure adhesive strength in the presence of water, the urethane film with the adhesive layer attached is attached to the weight ring without any slack, and 5 μL of water is dropped onto the adhesive layer that the probe comes into contact with. After that, measurements are performed using a test method that conforms to the probe tack test method in the 17th revision of the Japanese Pharmacopoeia. A SHIMADZU EZ-SX 100N is used for the measurements.
[0028] Relationship between coating film thickness and moisture permeability The raw resin for the film was Nipporan 2304 (Tosoh Corporation), and the coating thickness was adjusted to produce coated urethane films with thicknesses of 7, 20, 30, 40, and 50 μm after drying. Moisture permeability was measured using JIS L1099 A-1 method (calcium chloride method). The measurement results are shown in Table 1. It was found that the moisture permeability decreased as the thickness of the covering film increased. From the viewpoints of the stretchability of the covering film, the fit to the skin, and the fixation of the catheter, it was found that the thickness of the covering film is desirably 5 to 30 μm, and preferably 7 to 30 μm.
[0029] [Table 1]
[0030] Water-absorbent padding material and its water absorption capacity The amount of water absorption is determined by allowing the prepared water-absorbent pad material to absorb a sufficient amount of water, attaching the pad material to a petri dish, tilting it at an angle of 45 degrees to drain the water, and measuring the weight of the water retained in the pad material after one minute. The water absorption capacity of the water-absorbent pad material that can be used in the present invention is 0.01 g / cm 2 The results of the water-absorbing pad material used in Test Example 6-9 are shown in Table 2. From Table 2, the water-absorbing capacity of the water-absorbing pad material used in Test Example 6-9 is 0.1 to 0.4 g / cm 2 The range was.
[0031] [Table 2]
[0032] EXAMPLES
[0033] The present invention will now be described in more detail with reference to the following examples. These examples are merely illustrative of the present invention, and the scope of the present invention is not limited to these examples.
[0034] Preparation of the Dressing Composite (Example 1) 20% by mass of Rubiscol K-90 (polyvinylpyrrolidone) (BASF Japan Ltd.) was dissolved in ethanol as a water-absorbing component and added to HIPAS-10 (Cosmedy Pharmaceutical Co., Ltd.). 5% by mass of Cosmol-13 (octyldodecyl lactate) (The Nisshin Oillio Group, Ltd.) was then added and thoroughly stirred. The mixture was then coated on a release sheet and dried to produce a 20 μm thick adhesive layer. A water-absorbing pad material, Airlaid AL150N (basis weight 150 g / m) was then applied to this adhesive layer. 2 ) (Kinsei Paper Co., Ltd.) was applied in the shape shown in Figure 6, and then the covering film (urethane film with a thickness of 20 μm) produced in Test Example 2 was transferred to prepare a composite dressing material.
[0035] Preparation of Composite Dressing Material (Comparative Example 1) As Comparative Example 1, a dressing composite was prepared by removing only the water-absorbent component, Rubiscol K-90, from the composite of Example 1.
[0036] Preparation of the Dressing Composite (Example 2) In Example 2, 0.5% by mass of sodium hyaluronate (FCH-SU: Kikkoman Biochemifa Corporation) was dissolved in 5% by mass of purified water, and added to 94.5% by mass of HIPAS-10 (Cosmedi Pharmaceutical Co., Ltd.), mixed and stirred to prepare a suspension solution, which was then applied to a release sheet and dried to prepare a 30 μm thick adhesive layer. After attaching water-absorbent pad material urethane foam F2 (Fuji Rubber Industry Co., Ltd.) to this adhesive layer, the covering film (urethane film thickness 7 μm) produced in Test Example 1 was transferred to prepare a composite dressing material.
[0037] Preparation of Composite Dressing Material (Comparative Example 2) As Comparative Example 2, a dressing composite material was prepared from Example 2 except that 0.5% by mass of sodium hyaluronate was omitted.
[0038] Preparation of the Dressing Composite (Example 3) A composite dressing was prepared by adding 5% by mass of Pencel D-135, a polymerized rosin ester, to the adhesive of Example 1.
[0039] Test Example 10: Measurement of adhesive strength of adhesive layer Assuming that the dressing composite would be applied to skin contaminated with leaked exudate, whether or not the adhesive strength would decrease when water was applied to the dressing composite was confirmed. Measurement of adhesive strength without water on the adhesive layer was performed using a test method conforming to the probe tack test method of the 17th revision of the Japanese Pharmacopoeia. Measurement of adhesive strength with water on the adhesive layer was performed by dropping 5 μL of water onto the adhesive layer that the probe contacted, and thereafter using a test method conforming to the probe tack test method of the 17th revision of the Japanese Pharmacopoeia. Measurement of adhesive strength with and without water was performed using the adhesive layers prepared in Example 1 and Comparative Example 1. Units are N / cm 2 The results are shown in Tables 3 and 4.
[0040] [Table 3]
[0041] [Table 4]
[0042] As shown in Table 3, in an adhesive layer containing 10 mass% polyvinylpyrrolidone, the adhesive strength loss rate in the presence of water was 60%. Also, as shown in Table 4, in an adhesive layer containing no polyvinylpyrrolidone, the adhesive strength loss rate in the presence of water was 81%. As described above, it was revealed that the loss of adhesive strength can be suppressed by adding polyvinylpyrrolidone, a water-absorbent polymer, to the adhesive layer.
[0043] Test Example 12: Evaluation of composite dressings in the presence of moisture The composite dressings prepared in Example 2 and the composite dressings prepared in Comparative Example 2 were applied to the inner side of the forearm of five panelists with 1 mL of water dropped on the application site, and the composite dressings were observed after 24 hours. The condition of the composite dressings after 24 hours of application was scored using the scores shown in Table 5, and evaluated by the sum of the scores of the five panelists. The condition of the absorbent pad and the skin was observed after 6 hours of application, scored using the scores shown in Table 6, and evaluated by the sum of the scores of the five panelists.
[0044] [Table 5]
[0045] [Table 6]
[0046] [Table 7]
[0047] The results are shown in Table 7. In the composite dressing with sodium hyaluronate blended in the adhesive layer, the film remained in a state where it was difficult to peel off from the skin even after 24 hours. This is thought to be because, in the composite dressing with sodium hyaluronate blended in the adhesive layer, moisture in the pad is absorbed through the entire composite dressing and passes through, whereas in the composite dressing without sodium hyaluronate blended in the adhesive layer, the affinity for water is low and moisture does not easily pass through the adhesive layer.
[0048] Test Example 13: Evaluation of a composite dressing material containing a tackifier The composite dressing materials prepared in Examples 1 and 3 were applied to the inside of the forearm, and the state of detachment was observed when the composite dressing materials were removed after 24 hours. The state of detachment of the dressing materials was scored using the scores shown in Table 5, and the total score of the five subjects was used for evaluation.
[0049] [Table 8]
[0050] The results are shown in Table 8. The dressing material containing the tackifier Pencel D-135 in the adhesive layer had improved adhesion to the skin, and the sheet remained difficult to peel off from the skin even after 24 hours.
[0051] As shown in Figure 12, it is also possible to attach a tag 6 by making it easy to peel off the transparent or semi-transparent covering film with your fingers. There are no particular restrictions on the shape, color, or location of the tag, as long as it is recognizable. Examples of tag shapes and attachment locations are shown in Figures 13 to 16, but the present invention is not limited to these. [Explanation of symbols]
[0052] 1 Transparent or semi-transparent covering film 2 Adhesive layer 3. Water-absorbent padding 4 Release sheet 5 Catheter 6 Tags
Claims
1. Moisture permeability of 1,200g / m 2 A composite dressing material having a covering film having a life of 24 hours or more, an adhesive layer laminated on the entire surface of the covering film, and an absorbent pad material adhered to the adhesive layer, the adhesive layer comprises a hydrophilic acrylic adhesive or a urethane adhesive, or a mixture of these adhesives, and the adhesive layer further comprises one or more water-absorbing components selected from the group consisting of polyvinyl alcohol, polyvinylpyrrolidone, polyacrylamide, polyacrylic acid, sodium polyacrylate, methylcellulose, ethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, carboxymethylcellulose, alginic acid, propylene glycol alginate, agarose, chitosan, hyaluronic acid and hyaluronic acid derivatives, chondroitin sulfate, starch, pectin, tragacanth gum, xanthan gum, guar gum, and carrageenan; The absorbent pad material is a water-absorbent soft urethane foam or a pad having a basis weight of 100 g / m 2 A water-absorbent composite dressing material comprising the above nonwoven fabric.
2. 2. The absorbent dressing composite of claim 1, wherein a release sheet is attached to the side of the adhesive layer opposite to the side that contacts the cover film, and the absorbent pad material is enclosed between the cover film and the release sheet.
3. 2. The water-absorbent composite dressing material according to claim 1, wherein the adhesive layer has an adhesive strength of 0.4 N / 20 mm or more in the presence of moisture.
4. The water-absorbent dressing composite material according to claim 1, wherein the covering film is a polyurethane resin having a thickness of 5 to 30 μm, the adhesive layer is a composition containing an acrylic polymer having a thickness of 10 to 80 μm, and the water-absorbent component is contained in the adhesive layer at 0.1 to 30% by mass.
5. The water absorption capacity of the water-absorbing pad material is 0.01 g / cm 2 2. The absorbent dressing composite of claim 1.
6. The absorbent pad material has a rectangular or square shape with each side measuring 30 mm to 50 mm, a circular or elliptical shape with a diameter of 30 mm to 50 mm, and is hollowed out to a periphery of approximately 10 mm, so that exudate leaking from the catheter does not leak out.
7. 10. The absorbent dressing composite of claim 1, wherein the adhesive layer comprises a tackifier.
Citation Information
Patent Citations
dressing material
JP1993285224A
Dressing material
JP2014104055A
Dressing
JP2018000956A
Adhesive material
JP2021183051A